2002
DOI: 10.1002/jbm.10466
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo degradation of bioabsorbable PLLA spinal fusion cages

Abstract: The in vitro and in vivo degradation of poly-L-lactic acid cages used as an adjunct to spinal arthrodesis was investigated. In the in vitro experiments cages were subjected to aging up to 73 weeks in phosphate-buffered solution (pH 7.4) at 37 degrees C. Inherent viscosity, crystallinity, and mechanical strength were determined at different time points. In the in vivo study, the poly-L-lactic acid cages were packed with bone graft and implanted in the L3-L4 spinal motion segment of 18 Dutch milk goats. At 12, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 43 publications
1
35
0
4
Order By: Relevance
“…23,24,28 It was shown that degradation of the resorbable material occurred in a time-dependent and controlled way, resulting in high fusion rates. 23,24,26,29 Similar results were reported for a resorbable PLDLA device packed with autograft or rhBMP-2 in a sheep model. 30 Although the number of animals was small, the results were promising.…”
Section: Discussionsupporting
confidence: 53%
“…23,24,28 It was shown that degradation of the resorbable material occurred in a time-dependent and controlled way, resulting in high fusion rates. 23,24,26,29 Similar results were reported for a resorbable PLDLA device packed with autograft or rhBMP-2 in a sheep model. 30 Although the number of animals was small, the results were promising.…”
Section: Discussionsupporting
confidence: 53%
“…Lateral radiographs of the sectioned specimens were used to estimate interbody fusion within the cage devices according to a validated threepoint radiographic score, 36 as follows: radiographic Score 0, no ingrowth of bone into the cage; radiographic Score 1, ingrowth of bone with the cage securely fixed to vertebral bone above and below, but with a radiolucent discontinuity in the fusion mass; and radiographic Score 2, spondylosyndesis with solid bone bridging the fusion area. Similarly, the interbody fusion stage was determined on MR images, according to the same scoring range, but now expressed as MR Scores 0, 1, and 2.…”
Section: Analysis Of Fusionmentioning
confidence: 99%
“…2,6,8,9,23 Second, connective tissues need mechanical deformation to transport nutrients and waste products to and from the cells through the extracellular matrix, 16,21,24 and probably also to proliferate and differentiate; stiff implants relieve the load on living tissues and thus may retard or even inhibit interbody fusion (stress shielding). 14,28,[34][35][36]40 Therefore, the design and material of the spinal instrumentation largely determine clinical success.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bone formation rate and bone remodelling are elevated at 12 months, probably because of disintegration of the PLDLLA cages. Thereafter, PLDLLA cages were replaced with trabecular bone and dispersed fibrous tissue progressively [11,12].…”
Section: Discussionmentioning
confidence: 99%